Relationship between Gender, Subject Preference and Learning Styles - Suprihadi Suprihadi; Atik Rokhayani (Celt: A Journal of Culture, English Language Teaching & Literature, 2016)
Understanding the learning styles of the students is very crucial in implementing student-centered learning (SCL). The objectives of this research are to describe: 1) the general learning styles profile of the students of English Education Department Universitas Muria Kudus; 2) the dependency relationship between learning styles dimensions and gender, and 3) the dependency relationship between subject preference and learning styles dimensions. This research uses 208 students from different semesters as the samples, while the instrument is the Indonesian translation of Solomon-Felder Index of Learning Styles Questionnaire. The result of the analysis reveals that: 1) the general learning style profile of the students is balanced; 2) at ? .05, there is no significant relationship between the probability of the students of having certain learning styles dimensions and gender; 3) at ? .05, the subject preference of the students who are SensingIntuitive and Visual Verbal depends on their learning styles dimensions, while that of those who are Active Reflective and Sequential Global does not.